Reducing Tobacco Use through Taxation : The Experience of the Republic of Korea - World Bank Group (World Bank, Washington, DC, 2018)
As a country with one of the highest male smoking rates and one of the lowest cigarette prices in the world, Korea has prioritized many tobacco control efforts, including bans on smoking in public places, regulations on tobacco advertising, and public education about the harms of tobacco use. Consistent implementation of tobacco control policies has helped to magnify the importance of using tobacco tax rises as the basis of tobacco price policy – though these reforms took a long time to implement.